Hydroxyethylresorcinol- and hydroxyethylhydroquinone-containing poly(ethylene terephthalate) copolymers. (16th July 2021) - Mondschein, Ryan J.; Hostetler, Jon; Arrington, Clay B.; Long, Timothy E.
Abstract: Melt polycondensation incorporating meta -substituted hydroxyethylresorcinol (HER) or para -substituted hydroxyethylhydroquinone (HEH) regioisomers enabled the synthesis of poly(ethylene terephthalate) (PET)-based (co)polyesters with targeted comonomer mol %. Incorporation of either HER or HEH lowered the glass transition temperature ( T g ) relative to PET, but the 5% weight loss temperature ( T d, 5% ) remained unchanged. Similarly, the semi-crystalline morphology varied as a function of comonomer selection and mol % comonomer. Dynamic mechanical analysis confirmed decreasing β-relaxation intensities upon HER and HEH incorporation, while HER impacted β-relaxation intensity more substantially at similar mol %. HER incorporation also shifted the β-relaxation temperature ( T β ) to lower temperatures considerably more than HEH. Time-temperature-superposition (TTS) and Williams-Landel-Ferry (WLF) analysis of melt rheology probed various physical polymer properties including melt flow activation energy ( E a ), fractional free volume at T g ( f g ), and molecular weight of entanglement (Me ). HER-based (co)polyesters exhibited lower Ea compared to HEH. Likewise, HER incorporation lowered f g while HEH incorporation increased f g . HER-based (co)polyesters possessed a higher Me compared to HEH-based (co)polyesters, although both copolymers resulted in higher Me compared to PET. Tensile testing revealed HER/HEH-based (co)polyesters ultimate mechanical performance compared to amorphous PET. Both HER and HEH incorporation increased Young's moduli and yield strengths, although comonomer incorporation above 25–30 mol % yielded minimal change. Establishing structure-property relationships provided insight into the role of regioisomeric variation at various comonomer levels on thermal, rheological, and mechanical performance for PET-based copolymers. Graphical abstract: Image 1 Highlights: Hydroxyethylresorcinol & Hydroxyethylhydroquinone PET-modified polymers synthesized. Regioisomers correlated to polyester parameters and thermo-mechanical properties. meta- isomer more drastically altered properties compared to para- isomer. Both isomers reduced β-relaxation intensity & fractional free volume, f g Both isomers increased entanglement mol. weight, Young's modulus, & yield strength.